Pengembangan Media Reward Activity untuk Meningkatkan Disiplin Positif dan karakter Peserta Didik Kelas III Sekolah Dasar - Nur Afiffah; Hitta Alfi Muhimmah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This research aims to create a real character education media through a reward system called Reward Activity as a facility for teachers in controlling the discipline and politeness of third-grade elementary school students. This research uses R&D procedures with the ADDIE model which includes Analyze, Design, Develop, Implement and Evaluate. The subjects of this research were third-grade elementary school students at two schools, namely SDN 2 Sumberagung for small group trials and SDN Sambangrejo for large group trials. Information was obtained through interviews, observations, expert validation questionnaires, user reaction questionnaires and pretests and posttests. The research results show that the Reward Activity media has a media validity of 86% (very valid), practicality of 97% from students and 98% from teachers. The effectiveness test obtained high results with an N-Gain value of 0.75 for discipline character and 0.77 for politeness character. Based on the above data, the Reward Activity media is declared feasible, instant and efficient in improving the discipline and politeness of third-grade elementary school students.